La sucesión hereditaria de la posesión en el Perú desde 1984 hasta el 2022 - Casana Isern, Eduardo Javier (2023)
The present investigation was carried out with the purpose of addressing the problem of informality in terms of the possession of real estate in Peru. Once the problem was identified, the qualitative research method was chosen, with a practical action research design. The historical development of civil law institutions, such as possession, succession and acquisitive prescription of ownership, was analyzed. Savigny's subjective theory of possession and Ihering's objective theory of possession were analyzed. Likewise, we proceeded to analyze the development and evolution of possession through the civil codes promulgated in Peru. An analysis of law compared to the regulatory framework of Spain, France and Chile was also carried out. Of which legal figures were found as a result that validate the idea that possession can be acquired by succession, and these figures are civil possession (Spain) and possession saisine (France). Lastly, the main judicial resolutions were analyzed, in their different hierarchies, which recognize and/or point out the possibility that possession can be inherited. In conclusion, the hypothesis that possession can be inherited was confirmed, it is recommended to regulate this figure in Peruvian regulations and a bill is presented that can provide a solution to the problem encountered and that regulates the hereditary succession of possession in Peru.